Temperatures and interval geothermal-gradient determinations from wells in National Petroleum Reserve in Alaska - Blanchard, D.C.; Tailleur, I.L. (Geological Survey (U.S.). Western Region. Administrative Division., 1983)
Temperature and related records from 28 wells in the National Petroleum Reserve in Alaska (NPRA) although somewhat constrained from accuracy by data gathering methods, extrapolate to undisturbed formation temperatures at specific depths below permafrost, and lead to calculated geothermal graidents between these depths. Tabulation of the results show that extrapolated undisturbed temperatures range from a minimum of 98/sup 0/F (37/sup 0/C) at 4000 feet (1220 m) to a maximum of 420/sup 0/F (216/sup 0/C) at 20,260 feet (6177 m) and that geothermal gradients range from 0.34/sup 0/F/100' (6/sup 0/C/km) between 4470 feet to 7975 feet (Lisburne No. 1) and 3.15/sup 0/F/100' (57/sup 0/C/km) between 6830 feet to 7940 feet (Drew Point No. 1). Essential information needed for extrapolations consists of: time-sequential bottom-hole temperatures during wire-line logging of intermediate and deep intervals of the borehole; the times that circulating drilling fluids had disturbed the formations; and the subsequent times that non-circulating drilling fluids had been in contact with the formation. In several wells presumed near direct measures of rock temperatures recorded from formation fluids recovered by drill stem tests (DST) across thin (approx. 10-20 foot) intervals are made available. We believe that the results approach actual values close enough to serve as approximations of the thermal regimes in appropriate future investigations. Continuous temperature logs obtained at the start and end of final logging operations, conductivity measurements, and relatively long-term measurements of the recovery from disturbance at shallow depths in many of the wells will permit refinements of our values and provide determination of temperatures at other depths. 4 references, 6 figures, 3 tables.